2012
DOI: 10.1016/j.jpubeco.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Majority voting and the welfare implications of tax avoidance

Abstract: A benchmark result in the political economy of taxation is that majority voting over a linear income tax schedule will result in an inefficiently high tax rate whenever the median voter has a below average income. The present paper examines the role of tax avoidance for this welfare assessment. We find that the inefficiency in the voting equilibrium is the lower, the higher the average level of tax avoidance in the economy, or equivalently, the lower the median voter's amount of avoidance. The result holds for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…while the source used is limited to paper, there are no books or proceedings in it (Balestrino, 2010). This observation strategy was carried out in order to improve the quality of paper observations from several years ago and are constantly being updated to facilitate and enrich reader literacy (Traxler, 2012). In this case the problem referred to in this study is related to Tax Avoidance.…”
Section: Methodsmentioning
confidence: 99%
“…while the source used is limited to paper, there are no books or proceedings in it (Balestrino, 2010). This observation strategy was carried out in order to improve the quality of paper observations from several years ago and are constantly being updated to facilitate and enrich reader literacy (Traxler, 2012). In this case the problem referred to in this study is related to Tax Avoidance.…”
Section: Methodsmentioning
confidence: 99%
“…Summarizing, taxpayers are heterogeneous along two dimensions of the tax avoidance 'technology': with respect to attribute k j -determining the cost of as a foreign resident, and not on reported income. 9 See, e.g., Slemrod (2001) and Traxler (2012) for thorough treatments of the cost of underreporting in the context of tax avoidance. 10 We assume an interior solution x H (t; k j ) ≥ 0 for all types of taxpayers.…”
Section: Cheating On Income or On Residencementioning
confidence: 99%
“…In the same line as our study, both papers obtain equilibria in which preferences for income redistribution are nonmonotonic in taxpayers' income . Another paper in a similar line is Taxler (), which focuses on the welfare consequences of the possibility of tax avoidance in the standard model of redistributive policies. Taxler found that the higher the median voter's level of avoidance, the higher the inefficiency produced by the tax schedule chosen by majority vote.…”
Section: Introductionmentioning
confidence: 99%